To rewrite the quadratic function \( y = -2x^2 + 12x - 24 \) in vertex form by completing the square, we can follow these steps:
-
Factor out the coefficient of the \( x^2 \) term (which is \(-2\)) from the first two terms: \[ y = -2(x^2 - 6x) - 24 \]
-
Complete the square inside the parentheses. To do this, take the coefficient of \( x \) (which is \(-6\)), halve it (which gives \(-3\)), and then square it (which gives \(9\)): \[ y = -2(x^2 - 6x + 9 - 9) - 24 \] Rearranging gives: \[ y = -2((x - 3)^2 - 9) - 24 \]
-
Distribute the \(-2\): \[ y = -2(x - 3)^2 + 18 - 24 \]
-
Simplify the constant terms: \[ y = -2(x - 3)^2 - 6 \]
Now, the quadratic function in vertex form is: \[ y = -2(x - 3)^2 - 6 \]
The vertex of the function is at \((3, -6)\).